Color composition and its uses in the space of ontemporary Iraqi theatrical performance (Al-Academy, 2023)
Color composition represents a homogeneous number of colors, and the designer seeks to reshape color in a new way that is different from traditional theatrical performances. Color, through its works, forms different spaces and expresses different and renewed ideas and visions. Color goes beyond its plastic functions with pigments and lighting, as it carries social, historical and geographical features and connotations, and color creates a special awareness among the recipient to indicate the content of the theatrical performance.The research was divided into four chapters. The first chapter included (the methodological framework) and the second chapter included (theoretical framework), which included two sections: the first: the concept of color and its roots, and the second: the formation of color and its functions in the space of theatrical performance. The researcher extracted some indicators and data from the theoretical framework. The third chapter (research procedures) included the research community, research tools, indicators, sample observation, the descriptive analytical research method, then analysis of the research sample, a model of the play Blood Horse, prepared and directed, and scenography by director (Jabbar Jodi) and presented at the National Theater. The fourth chapter also included a presentation and discussion of the results, and the research concluded with a list of sources and references and a summary in English